Two Success Stories as Result of the Horizon Europe Shift-Hub Project - Koumpis, Adamantios; Stefanut, Paul; Spyroglou, Odysseas (International Journal of Online and Biomedical Engineering (iJOE), 2025)
This paper reflects on two success stories emerging from the Shift-Hub project, a publicly funded European Commission initiative. The first success story revolves around the concept and implementation of ‘DemoDays,’ designed to connect supply and demand in smart health innovation. Initially a contractual obligation, the project team chose to take ownership, transforming DemoDays from simple KPIs fulfilment into meaningful, sustainable events. They prioritised demonstrating tangible solutions over mere presentations, focusing on the principle of ‘to see is to believe’. Online format, concise two-hour duration, and a focus on recurring demonstrations contributed to their success. This approach emphasized commitment and risk-taking, contrasting with the common practice of risk aversion and diffused responsibility. The second success story, still in progress, concerns the exploration of smart health ecosystems. Departing from superficial definitions, the team identifies the complex and unique nature of individual ecosystems, recognizing that ‘every ecosystem is different in their own way’. Their research, focusing on mental health and cardiovascular disease ecosystems, highlighted the importance of context-specific analysis over generalized best practices.